2003
DOI: 10.3141/1823-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Applicability of Ultrathin Whitetopping in Florida

Abstract: A three-dimensional (3-D) finite element model for stress analysis of pavements with ultrathin whitetopping (UTW) under critical loading conditions was developed. The 3-D model developed was used to analyze the UTW test pavement sections at the Ellaville Weigh Station in Florida, which had less than satisfactory performance. The poorly performing UTW sections at the Ellaville Weigh Station were found to have relatively higher maximum computed stresses under critical loading conditions, which appeared to explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…However, software strains are always higher than field strains, which is more conservative and also it should be noted that the field load was a dynamic load while a static load was used in the analysis by the 3-D finite element model. It was found in a previous study that static strains are higher than dynamic strains (Kumara, 2005). Figure 4 shows the distribution of field strain and model strain data at all the locations.…”
Section: -D Finite Element Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, software strains are always higher than field strains, which is more conservative and also it should be noted that the field load was a dynamic load while a static load was used in the analysis by the 3-D finite element model. It was found in a previous study that static strains are higher than dynamic strains (Kumara, 2005). Figure 4 shows the distribution of field strain and model strain data at all the locations.…”
Section: -D Finite Element Model Developmentmentioning
confidence: 99%
“…The interface bond strength estimation was done through the Iowa shear test, which was performed at the Florida Department of Transportation laboratories. The test results indicated that interface bond strength is about 1.40 MPa (Kumara, 2005) and was considered as the bond strength in this study. In a thin whitetopping pavement, it is desirable to have a stress/ strength ratio of less than 0.5 and a shear stress at interface of less than the bond strength to avoid fatigue failure and bond failure, respectively.…”
Section: Determination Of Design Flexural Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…When the PCC overlay and asphalt layer are fully bonded, the pavement behaves as a composite pavement, reducing the tensile stress/strain at the bottom of the PCC overlay. This is supported by 3D-FEM studies (Nishizawa et al 2003 andKumara et al 2003) and by field observations (Vandenbossche 2003;Lin and Wang 2005). The lack of a good bond has been reported to be responsible for premature failure of whitetopping pavement (McMullen et al 1998;.…”
Section: Whitetopping Construction Practicesmentioning
confidence: 79%
“…Rasmussen (2004) reported that aggregate thermal properties (coefficient of thermal expansion (CTE), thermal conductivity, and specific heat) and aggregate gradation needed to be considered in the concrete mix design. The CTE is of interest considering that the literature shows that there is a significant increase in the stresses in the WT layer due to the thermal gradients (Roessler 1998; Kumara et al 2003;Lin and Wang 2005;and Wu et al 2007).…”
Section: Concrete Materialsmentioning
confidence: 99%